Influence of supply chain management on the sustainable construction industry in Algeria - Harouache, Ahmed; Abkar, Mahdi Mohammed Abdullah; Gamil, Yaser; Al-Shameri, Ahmed Saleh Ahmed; Gabir, Adham Ahmed Mohammed (Frontiers in Built Environment, 2024)
The construction industry is an important business sector that plays a vital role in providing physical equipment and infrastructure, with a significant indirect impact on other industries. This research investigates how supply chain management can improve sustainable construction practices in the Algerian construction industry, which plays a crucial role in providing physical infrastructure and equipment and indirectly affecting other sectors. The study aims to investigate the relationship between traditional supply chain management and sustainable construction in Algeria. To achieve the main goal of this study, a quantitative approach was used, data was collected through a survey consisting of 61 items using a five-point Likert scale. Data was gathered utilizing an online survey method. The participants are managers, supervisors, executives and suppliers in the Algerian construction industry. A total of 237 respondents from construction companies in Algeria participated in the study. The gathered data was analysed using Smart PLS, and the results of the partial least squares (PLS) path analysis confirmed the positive relationship between traditional supply chain management and sustainable construction. The findings of this study provided valuable insights for future stakeholders, including employers, designers, manufacturers, contractors, and suppliers, to enhance supply chain management practices for sustainable construction in Algeria. Therefore, this study provides results in terms of outstanding management and theoretical implications for the enhancement of the integration of sustainable supply chain management towards sustainable construction. This study has explored the issues of the relationship between traditional supply chain management and sustainable construction in Algeria.